The effect of finasteride, a 5 alpha-reductase inhibitor, on scalp skin testosterone and dihydrotestosterone concentrations in patients with male pattern baldness - Dallob, A L; Sadick, N S; Unger, W; Lipert, S; Geissler, L A; Gregoire, S L; Nguyen, H H; Moore, E C; Tanaka, W K (The journal of clinical endocrinology and metabolism, 1994)
The effects of the 5 alpha-reductase inhibitor, finasteride, on scalp skin testosterone (T) and dihydrotestosterone (DHT) levels were studied in patients with male pattern baldness. In a double blind study, male patients undergoing hair transplantation were treated with oral finasteride (5 mg/day) or placebo for 28 days. Scalp skin biopsies were obtained before and after treatment for measurement of T and DHT by high pressure liquid chromatography-RIA. In 10 male subjects studied at baseline, mean (+/- SEM) DHT levels were significantly higher in bald (7.37 +/- 1.24 pmol/g) compared to hair-containing (4.20 +/- 0.65 pmol/g) scalp, whereas there was no difference in mean T levels at baseline. In bald scalp from 8 patients treated with finasteride, the mean DHT concentration decreased from 6.40 +/- 1.07 pmol/g at baseline to 3.62 +/- 0.38 pmol/g on day 28. Scalp T levels increased in 6 of 8 subjects treated with finasteride. Finasteride decreased the mean serum DHT concentration from 1.36 +/- 0.18 nmol/L (n = 8) at baseline to 0.46 +/- 0.10 nmol/L on day 28 and had no effect on serum T. There were no significant changes in scalp or serum T or DHT in placebo-treated patients. In this study, male subjects treated with 5 mg/day finasteride for 4 weeks had significantly decreased concentrations of DHT in bald scalp, resulting in a mean level similar to the baseline levels found in hair-containing scalp.